(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. La blasphemy law - 3. Un campo di falsa, un sorso d’acqua e il “peccato” contro Asia Bibi - 4. La sentenza della Corte Suprema - 5. Leading case o moral suasion? “More sinned against than sinning”: the Pakistan Supreme Court and Asia Bibi case ABSTRACT: Asia Bibi case, a Christian woman falsely accused of being a blasphemer, finds her ‘judge in Berlin’ in the Supreme Court of Pakistan. The Court does not address the ratio legis of blasphemy law but points out how contrary to the spirit of Islam is the misuse of law for political purposes. The wide international echo of the case makes this SC verdict a possible leading case in theme of presumption of innocence.